2021
DOI: 10.3390/coatings11010075
|View full text |Cite
|
Sign up to set email alerts
|

Mucilages from Different Plant Species Affect the Characteristics of Bio-Mortars for Restoration

Abstract: The need for compatible materials for the preservation of cultural heritage has resulted in the revival of lime-based mortar technology and other applications. This work investigates the cohesion and integrity of lime mortars added with fresh mucilage extracted from five plants and evaluates their bioreceptivity for long-term durability. Specimens of lime mortars added with 2.5% of fresh mucilage extracted from Aloe vera, Cylindropuntia californica, Opuntia engelmannii, Opuntia ficus-indica and Salvia hispanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…And although in recent years the use of prickly pear, due to its properties, has attracted great interest not only in food research, but also in medicine and cosmetics, we have found few articles on its use in the field of conservation-restoration and only on its use as solidifying agent for lime mortars [22]. This confirms that our research is at least innovative, and considering the good results obtained, it would be appropriate to further investigate its applications in the conservation and restoration of paper and other materials.…”
Section: Discussionmentioning
confidence: 99%
“…And although in recent years the use of prickly pear, due to its properties, has attracted great interest not only in food research, but also in medicine and cosmetics, we have found few articles on its use in the field of conservation-restoration and only on its use as solidifying agent for lime mortars [22]. This confirms that our research is at least innovative, and considering the good results obtained, it would be appropriate to further investigate its applications in the conservation and restoration of paper and other materials.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of lime are highly valued, as it provides excellent adhesion, workability and plasticity, which is why it has been traditionally used in mortars [27]. Lime mortars have been employed to protect masonry structures from anthropogenic action and the moisture caused by rainwater, and often they incorporate biomaterials which can enhance their durability and provide useful properties to the mixtures, with an extended use of cactus mucilage [28,29]. Additionally, lime has been used in the region to stabilize the clayey soils and earthen components such as the adobes [20], reducing the vulnerability of these constructions to the effect of water.…”
Section: The Situation Of the Vernacular Architecture Of Michoacanmentioning
confidence: 99%
“…Limestone and lime-based mortars have been consolidated using plant biopolymers. Reported biopolymers have been sourced from Aloe vera, Cylindropuntia californica, Opuntia engelmannii, Opuntia ficus-indica, Salvia hispanica and Sida angustifolia [17,21]. Biopolymers are obtained in a range of extraction procedures, soaking leaves and other leafy tissues in batches of water and subsequently leaving them to be released into the bulk water.…”
Section: Bioconsolidation Techniquesmentioning
confidence: 99%